(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The significant increase in car ownership has been recognized as one of the main reasons for traffic congestion worldwide, especially in city centers. Park-and-ride (P&R) facilities, which are car parks where users can adjust to public transportation to carry on their journeys, have long been used as an effective solution to mitigate congestion issues without affecting traffic demand. However, literature on the optimal localization of these facilities using geospatial approaches are still emerging. Feasible locations of P&R facilities are of crucial importance not only for users but also to local authorities and the environment. The aim of this paper is to explore the significance of several factors affecting optimal locations of P&R using Analytic Hierarchy Process (AHP) and to propose a multi-criteria geospatial approach to locate optimal park and ride facilities in Karbala, Iraq. Three key aspects are tested in the localization process, including users’ coverage, accessibility to major roads, and area availability using Geospatial Tool. The case study on the holy city of Karbala in Iraq was implemented and the results show that the optimization model is proved to be powerful in providing more optimal locations of P&R facilities. The paper concludes with a discussion of the practical implications, research limitations and future research directions.